Marketing warfare - Ries, Al.; Trout, Jack. (New York McGraw-Hill, 1986)
Basing their techniques on successful military strategies, the authors provide practical frameworks to effectively market products, companies, and institutions and use case histories to demonstrate how each technique operates.
Includes index.
Keywords: Competencia; Mercadotecnia